Mediators of the effects of canagliflozin on heart failure in patients with type 2 diabetes - Li, J; Woodward, M; Perkovic, V; Matthews, DR; al., E (Elsevier, 2019)
Objectives The purpose of this study was to explore potential mediators of the effects of canagliflozin on heart failure in the CANVAS Program (CANagliflozin cardioVascular Assessment Study; NCT01032629 and CANagliflozin cardioVascular Assessment Study–Renal; NCT01989754). Background Canagliflozin reduced the risk of heart failure among patients with type 2 diabetes in the CANVAS Program. The mechanism of protection is uncertain. Methods The percentages of mediating effects of 19 biomarkers were determined by comparing the hazard ratios for the effect of randomized treatment from an unadjusted model and from a model adjusting for the biomarker of interest. Multivariable analyses were used to assess the joint effects of biomarkers that mediated most strongly in univariable analyses. Results Early changes after randomization in levels of 3 biomarkers (urinary albumin:creatinine ratio, serum bicarbonate, and serum urate) were identified as mediating the effect of canagliflozin on heart failure. Average post-randomization levels of 14 biomarkers (systolic blood pressure, low-density lipoprotein and high-density lipoprotein cholesterol, total cholesterol, urinary albumin:creatinine ratio, weight, body mass index, gamma glutamyltransferase, hematocrit, hemoglobin concentration, serum albumin, erythrocyte concentration, serum bicarbonate, and serum urate) were identified as significant mediators. Individually, the 3 biomarkers with the largest mediating effect were erythrocyte concentration (45%), hemoglobin concentration (43%), and serum urate (40%). In a parsimonious multivariable model, erythrocyte concentration, serum urate, and urinary albumin:creatinine ratio were the 3 biomarkers that maximized cumulative mediation (102%). Conclusions A diverse set of potential mediators of the effect of canagliflozin on heart failure were identified. Some mediating effects were anticipated, whereas others were not. The mediators that were identified support existing and novel hypothesized mechanisms for the prevention of heart failure with sodium glucose cotransporter 2 inhibitors.